The Role Of Educational Philosophies (Progressivism, Existentialism And Postmodernism) In The Development Of Indonesian Human Resources: A Literature Study Approach - Edwin, Edwin; Wayan Suastra, I; Tungga Atmadja, Anantawikrama; Nyoman Tika, I (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research examines the role of three schools of educational philosophy-Progressivism, Existentialism and Postmodernism in the development of adaptive and competitive Indonesian human resources. Progressivism emphasises experiential learning, preparing students with critical thinking and problem-solving skills relevant to real life. Existentialism, on the other hand, emphasises individual freedom and the search for meaning, supporting education as a means for self-discovery and social responsibility. Postmodernism, meanwhile, emphasises a plurality of perspectives and rejects single truths, teaching students to think critically and appreciate diversity. This research uses a literature study approach to synthesise various findings that support the important contributions of these three schools of philosophy in shaping an educational curriculum that is responsive to social change and global needs. The results show that the integration of these philosophical values in education can produce human resources which are not only technically intelligent but also have reflective, adaptive characters and are able to collaborate in a complex environment.